Navigating Airway Dilemmas in Massive Lung Abscess: A Case Report of Risking Rupture to Save Ventilation - Putri, Nurul Hazi; Fauzi, Zarfiardy Aska; Ananda, Pratama (Respiratory Science, 2025)
Background: Lung abscess is a necrotizing infection with cavitary lesions and air fluid levels, most often from aspiration, hematogenous spread, or bronchial obstruction. Despite better antibiotics, large abscesses remain difficult to manage, especially with respiratory failure and altered consciousness. Case: A 49-year-old woman with uncontrolled hypertension who presented with progressive shortness of breath, cough, and fever. On admission to the Respiratory Intensive Care Unit (RICU), the patient appeared acutely ill, with a Glasgow Coma Scale of E4M6V4 and signs of systemic inflammation, hypoalbuminemia, and elevated D-dimer. Chest imaging revealed a large cavitary lesion in the left lower lobe (9.4 × 12.5 × 12.4 cm) with segmental atelectasis. PaO₂/FiO₂ ratio was 210, indicating mild oxygenation impairment. Blood cultures yielded Staphylococcus haemolyticus. Due to declining consciousness and respiratory effort, the patient underwent endotracheal intubation with lung-protective ventilation. A chest tube was placed, draining 300 mL of purulent fluid. The patient improved clinically and radiographically and was discharged, with successful extubation and recovery over ten days. Discussion: This case shows that managing a massive lung abscess in a critically ill patient demands individualized, multidisciplinary decisions that balance airway protection, infection control, and procedural safety, using head-up RSI with minimal-pressure ventilation and early cuff inflation, strict lung-protective settings, and timely chest-tube drainage. Stabilization was achieved despite a negative sputum culture and Staphylococcus haemolyticus bacteremia, in the context of complicating comorbidities. Conclusion: Timely intubation and individualized drainage strategies using a multidisciplinary approach are essential in managing large pulmonary abscesses in critically ill patients.